Education to the public on improving a healthy diet for the prevention of gastritis disease - Syaharuddin; Fardi (Abdimas Polsaka, 2025)
Gastritis remains a common gastrointestinal disorder in the community and is closely associated with unhealthy dietary patterns, irregular eating habits, and limited public awareness of preventive measures. This community service program aimed to improve public knowledge and practices related to healthy nutritional behavior as an effort to prevent gastritis disease. The program was conducted in a community setting, utilizing a participatory health education approach that targeted adult community members. Educational activities included interactive lectures, group discussions, and the distribution of educational materials that focused on balanced nutrition, regular meal timing, avoidance of irritant foods, and adequate fluid intake. The program's implementation was carried out in three stages: preparation, implementation, and evaluation. During the preparation stage, educational materials were developed in accordance with evidence-based guidelines for preventing gastritis. The implementation stage involved direct education sessions facilitated by health professionals, while the evaluation stage assessed changes in participants’ knowledge and self-reported dietary practices using pre- and post-intervention questionnaires. The results showed a significant improvement in participants’ understanding of the risk factors for gastritis and the importance of maintaining a healthy diet. Participants demonstrated increased awareness of appropriate food choices, reduced consumption of spicy and acidic foods, and improved meal regularity after the intervention. The community expressed positive acceptance of the educational program and a willingness to adopt healthier dietary behaviors in their daily lives. In conclusion, public education on healthy nutritional practices is an effective community-based strategy for preventing gastritis. This program emphasizes the importance of ongoing health education and community engagement in promoting sustainable lifestyle changes and alleviating the burden of gastritis at the community level